Demystifying Investor-State Dispute Settlement (ISDS) - Roderick Abbott; Fredrik Erixon; Martina Francesca Ferracane (European Centre for International Political Economy (ECIPE), 2014)
Investor-State Dispute Settlement, a legal provision in Bilateral Investment Treaties (BITs) or other International Investment Agreements that gives investors a right to call for arbitration with a state, has recently become the centre of controversy in a debate over the Transatlantic Trade and Investment Partnership (TTIP). Critics argue that such a provision is either illegitimate, unnecessary, and/or does not have any positive influence on flows of Foreign Direct Investment (FDI). More radical critics argue that ISDS is a provision that allows big companies to sue governments when they have made democratic choices with negative consequences for companies. This study surveys the recent decade of ISDS activity. It concludes that the number of ISDS cases has continued to grow, and that the growth is concentrated to certain sectors with a high degree of government involvement or political patronage.
Keywords: 330